Compassion and the perceived rarity of plants can increase plant appreciation - Pavol Prokop; Kristína Belzárová; Ivana Tomanová Čergeťová (People and Nature)
Abstract Plants have traditionally been perceived as “less alive” and less attractive than animals, posing challenges for conservation initiatives. Previous efforts to address Plant Awareness Disparity (PAD) mainly focused on cognitive aspects, neglecting the role of the affective domain. In our study involving a sample of Slovak individuals, we explored whether plants evoke compassion similar to that for animals and non‐living objects, and whether the perceived rarity of plants influences participants' willingness to pay (WTP). Results showed that withered and water‐stressed plants elicited compassion responses comparable to those for abused animals, whereas non‐living objects (dilapidated buildings before reconstruction) received significantly lower compassion scores. Participants expressed a lower WTP for plants compared to animals or minerals. The perceived rarity of plants, animals and minerals was positively correlated with the increase in WTP. As predicted, WTP positively correlated with conservation attitudes. Our findings highlight the potential to emphasize the affective domain and rarity in addressing PAD, both in science education lessons and conservation campaigns. This underscores the importance of recognizing and cultivating emotional connections with plants to enhance conservation efforts. Read the free Plain Language Summary for this article on the Journal blog.